Silencing of a Wheat Ortholog of Glucan Synthase-Like Gene Reduced Resistance to Blumeria graminis f. sp. tritici - Cheng, Peng; Wang, Zihao; Ren, Yanyan; Jin, Pengfei; Ma, Kangjie; Li, Qiang; Wang, Baotong (Frontiers in Plant Science, 2021)
Wheat powdery mildew, caused by the obligate biotrophic ascomycete fungal pathogen Blumeria graminis f. sp. tritici (Bgt), is a major threat to wheat production worldwide. It is known that Arabidopsis thaliana glucan synthase-like 5 (AtGSL5) improves the resistance of wheat to powdery mildew by increasing its anti-penetration abilities. However, the function of glucan synthase-like (GSL) orthologs in crop species remains largely unknown. In this study, TaGSL22, a novel functional ortholog of AtGSL5, was isolated as the only Bgt-induced GSL gene in wheat. Phylogenetic analysis indicated that TaGSL22 was conserved within the group of Gramineae and showed a closer relationship to GSL orthologs from monocots than to those from dicots. The TaGSL22 transcript was highest in the wheat leaves, followed by stems then roots. TaGSL22 was localized in the cell membrane and cytoplasm of wheat protoplasts, as predicted by transmembrane structure analysis. In addition, expression of TaGSL22 was induced by the plant hormones ethylene (ETH) and salicylic acid (SA), but down-regulated by jasmonate (JA) and abscisic acid (ABA). The transcript level of TaGSL22 was up-regulated in the incompatible interaction between Bgt and wheat, whereas it remained relatively unchanged in the compatible interaction. Knocking down of TaGSL22 by virus-induced gene silencing (VIGS) induced a higher infection type in the wheat-Bgt interaction. The TaGSL22-silenced plants exhibited reduced resistance to Bgt, accompanied by decreased callose accumulation. Our study shows a conserved function of GSL genes in plant immunity associated with penetration resistance, and it indicates that TaGSL22 can be used to improve papilla composition and enhance resistance to wheat powdery mildew.